Effects of Chemical and Natural Additives on Cucumber Juice’s Quality, Shelf Life, and Safety - Mohamed T. El-Saadony; Mohamed F. Elsadek; Alaa S. Mohamed; Ayman E. Taha; Badreldin M. Ahmed; Ahmed M. Saad (Foods, 2020)
Microbial contamination affects beverages’ lifetime, quality, and safety. Cucumber crops are seasonally spoiled because of the overproduction. The current study aimed to maximize the importance of natural preservatives and reduce the usage of artificial ones to prolong the cucumber juice’s storage life, enhance flavor, and control the microorganisms after protein isolate and organic acids supplementation. The additions included control (no addition), citric, benzoic acid, sodium salts, kidney bean pepsin hydrolysate (KPH), chicken egg protein isolate (CEPI), duck egg protein isolate (DEPI), and quail egg protein isolate (QEPI) as J-Control, J-Citric, J-Benzoic, J-sod. Citrate, J-sod. Benzoate, J-KPH, J-CEPI, J-DEPI, and J-QEPI, respectively. The antioxidant activity of these additives and juices was evaluated by DPPH radical scavenging activity. The antimicrobial activity, including antibacterial and antifungal activities, was evaluated by using disc assay and the radial growth of fungal mycelium, respectively. The phenolic compounds and flavonoids were estimated by a spectrophotometer as Gallic acid equivalent (GAE) and quercetin equivalent (QE), respectively. Moreover, chemical parameters such as pH, total soluble solids (TSS), Titratable acidity (TTA), and Vitamin C were evaluated by AOAC. Finally, the color properties were estimated by a spectrophotometer, using the Hunter method. KPH had higher significant (p ≤ 0.05) antioxidant activity (88%), along with antimicrobial activity. It significantly (p ≤ 0.05) reduced the growth of G+ and G− bacteria by 71–97% and 58–66% respectively. Furthermore, it significantly (p ≤ 0.05) inhibited the tested fungi growth by 70–88% and the other additives less than that. During the storage of cucumber juice for an interval of zero, two, four, and six months, the phenolic compounds and flavonoids were significantly (p ≤ 0.05) decreased. Consequently, the potential activity of the juice was reduced; in addition, pH and vitamin C were significantly (p ≤ 0.05) decreased during the storage period. Meanwhile, the TSS and Titratable acidity were significantly raised. As for color and sensory properties, J-sod. Benzoate, J-KPH, J-CEPI, and J-DEPI had significantly (p ≤ 0.05) high scores in color, taste, and flavor against the control. Generally, the usage of natural additives extends the cucumber juice’s lifetime and increased the manufacture of high-quality and valuable juice.